Comparative Clinical Study Of Rohitakadya Churna Ghana Vati with Vardhaman Pippali Rasayan in Alcoholic Liver disease. - Bandopadhyaya, Anindolok; Gupta, Piyush; Sharma, Anita (International Research Journal of Ayurveda & Yoga, 2020)
It is the major cause of liver disease in western as well as our countries. Although steatosis (fatty liver) & Alcoholic Hepatitis will develop in any individual who consumes a large quantity of alcoholic beverages over a long period of time, this process is transient and reversible. So in present study “Comparative Clinical Study Of Rohitakadya Churna Ghana Vati with Vardhaman Pippali Rasayan in Alcoholic Liver disease” we try to conclude out the efficacy of Ayurvedic treatment on Alcoholic liver disease. Group A contains Rohitakadya Churna Ghan Vati & Vardhaman Pippali Rasayan and Group B contains Phalatrikadi Kwath Ghan Vati & Vardhaman Pippali Rasayan. The data collection, analysis and conclusion drawn from it is elaborated in this article.